Climate change mitigation and adaptation as a sustainable regional development strategy: lessons from the Selangor River Basin, Malaysia - Chee, Ping Ngang; Halimaton Saadiah Hashim,; Joy Jacqueline Pereira, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2017)
Spatial planning practice in Malaysia has given greater prominence to environmental matters since the amendment of the Town and Country Planning Act 1976 in 1995, in which sustainable development has become the core emphasis of all planning policies and plans. However, climate change elements, which are necessary to be addressed in strategic planning, have not been explicitly incorporated in spatial plans that cover urban and rural areas at state and local levels. This paper presents a framework to evaluate the extent of spatial planning responses to climate change adaptation and mitigation across various critical components that defines the quality of plan, including facts, analysis, goals, policies and implementation, in the case of the Selangor River Basin, a river basin that can be considered as a life support in the Kuala Lumpur Conurbation, the biggest urban mega region in Malaysia. A content analysis of national, state and local level spatial plans reveals that quality of plans is higher at the national level but gradually decline towards the lower tiers plans, and that generally equal emphasis has been paid to both climate change mitigation and adaptation. The findings support the argument that spatial planning provides a platform for coordinating mitigation and adaptation responses through its sustainable development policies, however the scope of sustainable development in Malaysia need to be reframed for this purpose.